Monetary Policy Committees: meetings and outcomes - Jan Marc Berk; Beata K. Bierut (European Central Bank (ECB), 2009)
Monetary Policy Committees differ in the way the interest rate proposal is prepared and presented in the policy meeting. In this paper we show analytically how different arrangements could affect the voting behaviour of individual MPC members and therefore policy outcomes. We then apply our results to the Bank of England and the Federal Reserve. A general finding is that when MPC members are not too diverse in terms of expertise and experience, policy discussions should not be based on pre- prepared policy options. Instead, interest rate proposals should arise endogenously as a majority of views expressed by the members, as is the case at the Bank of England and appears to be the case in the FOMC under Chairman Bernanke.
Keywords: E58; D71; D78; 330; Bank of England; Federal Open Market Committee; monetary policy committee; voting; Geldpolitik; Zentralbank; Gruppenentscheidung; Großbritannien; USA